SISTEM LAYANAN ADMINISTRASI PENERIMAAN SAKRAMEN DI GEREJA RATU DAMAI PAROKI FULUR KABUPATEN BELU NUSA TENGGARA TIMUR - Mau, Kalistus Karavario; Igon, Skolastika Siba (Jurnal Publikasi Manajemen Informatika, 2026)
Ratu Damai Church of Fulur Parish is one of the Catholic churches in Belu Regency that serves the congregation in receiving the sacraments, such as Baptism, Eucharist, and Marriage. However, the administration process for receiving the sacraments has so far been carried out manually, so that problems often occur such as loss of important data, inaccurate recording, inefficient processes, and lack of accessibility of information for the congregation. This has an impact on the declining quality of service and congregation involvement in church activities. To answer these problems, this study aims to design and build a web-based sacrament reception administration service system that is able to digitize the registration process, data processing, and certificate printing. The system was developed using the Waterfall method, which includes the stages of needs analysis, design, implementation, and maintenance. The technologies used include PHP, MySQL, and Visual Studio Code. The results of the system implementation show a significant increase in admin work efficiency, recording accuracy, and ease of access to information for the congregation. This system provides online registration features, congregation and sacrament data management, and more orderly and secure documentation. This study is limited to the service of three types of sacraments: Baptism, Eucharist, and Marriage in the Queen of Peace Church, Fulur Parish.